2014
DOI: 10.1891/1058-1243.23.3.124
|View full text |Cite
|
Sign up to set email alerts
|

Birth, Bath, and Beyond: The Science and Safety of Water Immersion During Labor and Birth

Abstract: The 2014 objection to birth in water voiced by both the American Academy of Pediatrics and the American This article reviews the retrospective literature on water birth and explains newborn physiology and the protective mechanisms that prevent babies from breathing during a birth in water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 33 publications
0
14
0
3
Order By: Relevance
“…Considering the critical role of nurses and midwives in the birthing process, this situation could limit the labour pain management options that expectant mothers have to choose from and may lead to sub-optimal labour pain relief. Non-pharmacological interventions such as water immersion [32], guided imagery, aromatherapy, chromotherapy, homoeopathy, acupuncture, transcutaneous electrical nerve stimulation (TENS), floral therapy, and energy-level support [33] have been shown to be successful in reducing labour pain in other settings. The use of these other non-pharmacological pain management interventions could be explored further in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the critical role of nurses and midwives in the birthing process, this situation could limit the labour pain management options that expectant mothers have to choose from and may lead to sub-optimal labour pain relief. Non-pharmacological interventions such as water immersion [32], guided imagery, aromatherapy, chromotherapy, homoeopathy, acupuncture, transcutaneous electrical nerve stimulation (TENS), floral therapy, and energy-level support [33] have been shown to be successful in reducing labour pain in other settings. The use of these other non-pharmacological pain management interventions could be explored further in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the reduced consumption of analgesics and their associated side effects when non-pharmacologic techniques are used to complement pharmacologic interventions. Moreover, several studies have demonstrated the effectiveness of non-pharmacological methods in reducing labour pain [28,32,38]. Exposure to and utilisation of diverse types of non-pharmacological methods could contribute to reducing the perception that these methods do not really relieve pain and this could be achieved through frequent training sessions on these lesser known methods.…”
Section: Discussionmentioning
confidence: 99%
“…Waterbirth is highly controversial in the United States, [1][2][3][4][5][6][7][8] despite being an accepted practice in other high-resource nations. [9][10][11][12] Proponents of waterbirth cite anthropological evidence from Odent and Tjarkovsky regarding childbearing traditions that include immersion 13,14 ; the maternal benefits of laboring in water, such as pain relief and reduced stress on tissues secondary to buoyancy 15,16 ; the potential benefits to a neonate of being born into a warm, liquid environment similar to the amniotic fluid 17 ; and a series of studies, mostly small and observational, suggesting no adverse effects for either the laboring woman or the neonate.…”
Section: Introductionmentioning
confidence: 99%
“…Water also has an important role in the further development of every human (Balaskas, 2010, p. 144). If we ask ourselves how to increase the naturalness of birth, the answer is very simple: the only thing we have to do is add water (Harper, 2014).…”
Section: Why Did the Phenomenal Maternity Hospital In Vrchlabí Close?mentioning
confidence: 99%
“…Indigenous women from Western Australia paddled out to sea; they came back and gave (Kitzinger, 2012). Již v roce 1849 řekla americká lékařka, že každá žena potřebuje mít k normálnímu porodu teplou mysl (Harper, 2014).…”
Section: History Of Water Birthsunclassified